PENGARUH PEMBELAJARAN AKTIF MIKiR BERBASIS BUDAYA MELAYU MATERI OPERASI HITUNG TERHADAP HASIL BELAJAR DAN KESADARAN BUDAYA SISWA SEKOLAH DASAR - Iranti, Agna Dewi; Putra, Zetra Hainul; Alim, Jesi Alexander (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to examine the influence of MIKiR (Building Creative Ideas with Reality Innovation) active learning based on Malay culture on the learning outcomes and cultural awareness of elementary school students. This research was carried out at SDN 006 Sorek Dua and SDN 008 Dundangan with a quasi-experimental study approach for class II students. The variables studied were student learning outcomes in arithmetic operations material and cultural awareness which includes students' knowledge and appreciation of Malay culture. The learning method used focuses on applying Malay cultural values ​​in active learning activities to increase student motivation and understanding. Data was collected through learning outcomes tests, observations, and cultural awareness questionnaires. The research results showed that there was a significant increase in student learning outcomes in arithmetic operations and cultural awareness material after implementing MIKiR active learning based on Malay culture. Thus, Malay culture-based learning can contribute positively to academic achievement and instilling cultural values ​​in students. It is hoped that this research can become a reference in developing a curriculum that integrates academic learning with local culture to improve the quality of education in elementary schools